Fermentation and valorization of watermelon (Citrullus lanatus) rind wastes into livestock feed using Aspergillus niger and Mucor sp. - Ephraim Ekloh; Levi Yafetto (Scientific African, 2024)
Agro-industrial wastes pose environmental health hazards to humans and animals; yet, they are abundant, readily availabile and cheap, and therefore provide opportunities for their valorization with microorganisms to produce value-added, nutrient-rich animal feed. This study (i) determined, in vitro, optimum growth conditions for Aspergillus niger and Mucor sp. and (ii) subsequently evaluated their ability to ferment and valorize watermelon wastes for protein enhancement. Changes in protein contents of sterilized and unsterilized watermelon substrates were determined after 5, 10, and 15 days of fermentation with mono- and co-cultures of A. niger and Mucor sp. at 25 °C. Different growth conditions (pH, temperature, different concentrations of ammonium nitrate, sodium nitrate, urea, sodium chloride and thiamine) of synthetic media variously supported mycelial growth of A. niger and Mucor sp., either as mono- or co-culture; optimum growth conditions were selected for fermentation of watermelon wastes. Protein contents of sterilized and unsterilized watermelon substrates were enhanced by fermentation: (i) percentage increase in protein contents of sterilized watermelon fermented with mono-cultures of A. niger, Mucor sp. and co-culture of A. niger and Mucor sp. were 35.91, 18.94 and 22.18 %, respectively; (ii) protein contents in unsterilized watermelon substrates also increased by 23.94, 9.49, and 14.88 % for mono-cultures of A. niger and Mucor sp. and their co-culture, respectively. Overall, the observed trend in the increase of protein contents in the sterilized and unsterilized substrates by the test fungi was: mono-culture of A. niger > co-culture of A. niger and Mucor sp. > mono-culture of Mucor sp. Crude fat, fiber and ash contents significantly (p ≤ 0.05) decreased in both sterilized and unsterilized watermelon substrates, whereas the carbohydrate content increased significantly (p ≤ 0.05) in the substrates. These findings highlight the potential of watermelon waste as valuable bioresource and feedstock for valorization into livestock feed through fungal biotechnology. Future works to augment findings are suggested.